Headspace single drop microextraction versus dispersive liquid-liquid microextraction using magnetic ionic liquid extraction solvents - An, Jiwoo; Rahn, Kira L.; Anderson, Jared L. (Talanta (Oxford), 2017)
A headspace single drop microextraction (HS-SDME) method and a dispersive liquid-liquid microextraction (DLLME) method were developed using two tetrachloromanganate ([MnCl42-])-based magnetic ionic liquids (MIL) as extraction solvents for the determination of twelve aromatic compounds, including four polyaromatic hydrocarbons, by reversed phase high-performance liquid chromatography (HPLC). The analytical performance of the developed HS-SDME method was compared to the DLLME approach employing the same MILs. In the HS-SDME approach, the magnetic field generated by the magnet was exploited to suspend the MIL solvent from the tip of a rod magnet. The utilization of MILs in HS-SDME resulted in a highly stable microdroplet under elevated temperatures and long extraction times, overcoming a common challenge encountered in traditional SDME approaches of droplet instability. The low UV absorbance of the [MnCl42-]-based MILs permitted direct analysis of the analyte enriched extraction solvent by HPLC. In HS-SDME, the effects of ionic strength of the sample solution, temperature of the extraction system, extraction time, stir rate, and headspace volume on extraction efficiencies were examined. Coefficients of determination (R2) ranged from 0.994 to 0.999 and limits of detection (LODs) varied from 0.04 to 1.0μgL−1 with relative recoveries from lake water ranging from 70.2% to 109.6%. For the DLLME method, parameters including disperser solvent type and volume, ionic strength of the sample solution, mass of extraction solvent, and extraction time were studied and optimized. Coefficients of determination for the DLLME method varied from 0.997 to 0.999 with LODs ranging from 0.05 to 1.0μgL−1. Relative recoveries from lake water samples ranged from 68.7% to 104.5%. Overall, the DLLME approach permitted faster extraction times and higher enrichment factors for analytes with low vapor pressure whereas the HS-SDME approach exhibited better extraction efficiencies for analytes with relatively higher vapor pressure. [Display omitted] •Magnetic ionic liquids are used as solvents in headspace single drop microextraction.•Tetrachloromanganate-based MILs exhibit low UV absorbance and are HPLC compatible.•A rod magnet can be used to sustain a microdroplet of MIL during HS-SDME.•MILs were used in HS-SDME and DLLME for the determination of 12 aromatic analytes.•The HS-SDME approach provided higher enrichment of analytes with higher volatility.